2022
DOI: 10.3934/agrfood.2022010
|View full text |Cite
|
Sign up to set email alerts
|

Peaberry and normal coffee bean classification using CNN, SVM, and KNN: Their implementation in and the limitations of Raspberry Pi 3

Abstract: <abstract> <p>Peaberries are a special type of coffee bean with an oval shape. Peaberries are not considered defective, but separating peaberries is important to make the shapes of the remaining beans uniform for roasting evenly. The separation of peaberries and normal coffee beans increases the value of both peaberries and normal coffee beans in the market. However, it is difficult to sort peaberries from normal beans using existing commercial sorting machines because of their similarities. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
2
12
0
1
Order By: Relevance
“…It is seen in all the states that in the three states, the peaberry's width and thickness did not present considerable variation, with a difference lower than 1 mm, consistent with the fact that their shape is ellipsoidal (Gope & Fukai, 2022;González et al, 2019), implying that the peaberries were more homogeneous disregarding the state.…”
Section: Orthogonal Dimensionssupporting
confidence: 58%
“…It is seen in all the states that in the three states, the peaberry's width and thickness did not present considerable variation, with a difference lower than 1 mm, consistent with the fact that their shape is ellipsoidal (Gope & Fukai, 2022;González et al, 2019), implying that the peaberries were more homogeneous disregarding the state.…”
Section: Orthogonal Dimensionssupporting
confidence: 58%
“…6 ). Because normal fertilization leads to the independent development of two embryos into regular coffee beans whereas the maturation of only a single embryo generates peaberry coffee bean [ 30 ]. The characterization of lipid metabolism along flavonoid biosynthesis-associated genes could help to reveal how abortion of a single embryo from two embryos leads to peaberry coffee beans instead of regular beans.…”
Section: Resultsmentioning
confidence: 99%
“…Usually coffee fruit cherry has two embryos, their fertilization generate two independent hemispherical shape beans. However, sometimes only one embryo is further developed to yield round shape thicker bean which is commonly known as a peaberry [ 30 ]. The probability of peaberries occurrence is extremely low under normal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The model reports an accuracy of over 80% [20]. Previous studies have shown the availability of image processing and machine learning techniques, in [21] is reported the application of techniques such as Convolutional neural networks (CNNs), Support vector machines (SVMs), and k-Nearest-neighbors (KNNs), for the classification of peaberries and normal beans. The separation of peaberries and normal coffee beans increases the value of both peaberries and normal coffee beans in the market.…”
Section: Related Workmentioning
confidence: 99%